Actuating Reading Comprehension through Genre-Based Directed Reading Thinking Activities (G-BDRTA) Viewed from Critical Thinking Skills - Ahmad Hanan; Muhammad Muhlisin; Taufik Suadiyatno (Journal of Languages and Language Teaching, 2020)
The significance of reading comprehension for learners’ English mastery makes English teachers need to help learners to activate their background knowledge related to texts being read and promote the use of reading techniques. In this study, researchers applied the genre-based directed reading thinking activities (G-BDRTA). Genres here are oriented to provide learners with various text types for reading activities. Consequently, this study was aimed at actuating learners’ reading comprehension through genre-based directed reading thinking activities (G-BDRTA) viewed from critical thinking skills. This study was classified as an experimental study using non-equivalent control group design. This study was conducted at SMAN 1 Lingsar. There were 62 learners involved in this study. The learners were divided into two groups and each group embraces 31 learners. One group becomes an experimental group which is subjected to the G-BDRTA strategy and the other group is subjected to the control group treated using student-team-learning (STL) strategy. To find out the data, researchers used a reading test and critical thinking test as research instruments. Then, the data were analyzed using Two-Way-ANOVA. Based on the data analysis, there is a significant effect of G-BDRTA strategy on students’ reading comprehension viewed from critical thinking skills.